PEMERIKSAAN KECACINGAN (SOIL TRANSMITTED HELMINTHS) DENGAN PENGARUH PHBS PADA ANAK DI DESA KARADENAN KABUPATEN BOGOR - Kurniawan, Muhammad Rizki; Nirwana, Rima; Yansen, Aturut (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2024)
Background: Worms are a parasitic infection in the form of worms entering the human body. One of the factors that causes worms is personal hygiene. The aim of the research is to study the relationship between risk factors and the effects of worms on children's health. Objectives: One place that has a risk of worms is the village of Keradenan, Bogor district, because the condition of the village is slum. Materials and Methods: This type of research is analytical with a cross sectional research design. The sample in this study was 96 people who met the inclusion and exclusion criteria using a purposive sampling technique. Data collection was carried out by filling out questionnaires and checking for worms (soil transmitted helminths) using native methods. Data processing uses statistical software with the Chi square test. Results: The incidence of worms was 13.54% of the 96 samples of the type of Soil Transmitted Helminthes worm that infects children, namely Ascaris Lumbricoides. Conclusions: Based on the results of the research, there is an influence on clean and healthy living behavior on the children of the village of Keradenan, the result of worm examinations is that the number of worms has decreased.